Analisis Kekuatan Tekan Selubung Komposit Laminat E-glass pada Beton Kolom Silinder dengan Metode Vacuum Bagging - Siregar, Doni Alfiah; Zulfikar, Achmad Jusuf; Siahaan, M. Yusuf Rahmansyah; Siregar, Rakhmad Arief (Rekayasa Material, Manufaktur dan Energi, 2022)
This study aims to obtain the average compressive strength of cylindrical column concrete specimens reinforced with an e-glass fiber laminate composite wrap based on variations in the number of wraps. In addition, in this study, the compressive strength and damage patterns will be analyzed to obtain the performance of the sheath in the concrete structure. The test specimens were molded according to the ASTM C39 standard with a diameter of 50 mm and a length of 150 mm. The process of applying laminated composite wrap to concrete specimens is carried out using the vacuum bagging method. The compressive strength test on the specimen is carried out by providing an axial load on the specimen until it failures. The results obtained are that the compressive strength of the specimen has increased significantly due to the provision of e-glass fiber wrap. A significant increase in the compressive strength of concrete specimens occurred in 3 layers of e-glass fiber wrap which reached more than 60%. Furthermore, the ability of the e-glass fiber wrap in protecting the cylindrical concrete structure due to the applied load also experienced an increase in performance in the 2 and 3 layers of the e-glass fiber wrap.